Adaptação e validação do restq-coach para a população brasileira de treinadores esportivos e análise dos constructos de estresse, recuperação e sintomas da síndrome de Burnout - Varley Teoldo da Costa (2011)
The aim of this study was to test the original proposal of the RESTQ-Coach instrument, by Kallus and Kellman (1993); as well as to validate the Brazilian version of the questionnaire and measure the stress levels, recuperation and burnout probability symptoms of Brazilian coaches. The sample was composed of 424 federated coaches, who were evaluated using the Brazilian version of the RESTQ-Coach. The first result was not confirmed, through the confirmatory factorial analyses (CFA) of the original organized structure of the instrument. Besides that, the best factorial solution to validate the Brazilian version of the RESTQ-Coach were the 6 constructs: general stress, specific stress, recovery, self efficacy, physical well-being, and cognitive techniques domains. The measurements adjusted indicators for 6 constructs were CFI= .96, TLI= .95 and RMSEA= .07, that aggregates to the content validation from the judges do confirm the quality of the instrument in the Brazilian version. The results from the coaches shown smaller scores of perception of general and specific stress when compared with recovery, which shows a lack of burnout syndrome in these samples. Also identified were high scores of self efficacy and physical well-being. It was concluded that the original proposal by Kallus and Kellmann (1993) is not valid for the samples of Brazilian coaches. The Brazilian version of the instrument is composed of 6 constructs and the Brazilian coaches are self-evaluated as efficient professionals that show small levels of stress, good recovery capacity and small capacity to become burnout syndrome